Perceptions and preparedness of K-12 educators in adopting generative AI - Juhee Kim (Research in Learning Technology)
The integration of generative artificial intelligence (AI) tools, such as ChatGPT and DALL-E, presents transformative opportunities and challenges for K-12 education. This mixed-methods study investigates educators’ perceptions, familiarity, and preparedness for AI adoption, as well as institutional strategies and barriers. Quantitative findings indicate strong relationships between AI familiarity, perceived readiness, and institutional planning stages. Qualitative analysis highlights challenges such as insufficient professional development, ethical concerns, and infrastructural inequities, alongside opportunities for enhancing personalised learning and operational efficiency. The findings underscore the need for targeted training, equitable resource access, and clear institutional policies to ensure effective and ethical AI integration. This research offers actionable insights for educators, policymakers, and leaders seeking to navigate AI’s potential in K-12 education.